(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2025)
Floral are one of the elements that leads to therapy, healing, and aromatic vibes in the spa design. One of the floral specialties is its scent. Scent and interior design combine to create a complex and nuanced pattern of sensory elements that maximizes any space’s potential. The emphasis of floral elements towards space will trigger human’s senses and be able to impact their mood and emotions. Spa has become one of the most important healing spaces for humans to improve their well-being and reduce stress. However, some of the spa interiors are unable to produce positive atmosphere and customers are unable to experience the therapeutic vibe into the space. Interior smell is frequently overlooked in spa interior design, yet it can significantly impact the overall atmosphere of the area. This is because the sense of smell is an unseen or an invisible component when it comes to interior design. This paper aims to develop people’s knowledge regarding to the importance and effect of the floral fragrance towards spa interior design that will help to improve human’s well-being. Next focus is to find out how floral fragrance in spa designs act to create a healing environment which means how to use this element in an effective way. The method that will be used in this study is qualitative and quantitative method. All information will be collected by finding some of the case studies or articles that relate to the purpose. Furthermore, this research will be strengthened by distributing a questionnaire form to 30 respondents regarding the importance and effect of floral scent on spa interior design and human well-being. This research report reveals that most respondents strongly believe that floral scents surely have a lot of beneficial impact towards spa interior design and human mood and emotions. Thus, scent is also considered as an essential sense when it comes to spa interior design.